Empirical methods for reference evapotranspiration estimation - Sobrinho, Oswaldo Palma Lopes; Júnior, Wady Lima Castro; Santos, Leonardo Nazário Silva dos; Silva, Gerlange Soares da; Pereira, Álvaro Itaúna Schalcher; Tavares, Germanna Gouveia (Scientia Agraria Paranaensis, 2020)
The reference evapotranspiration (ETo) is a parameter applied in meteorological, climatological and hydrological studies being of great importance for the planning, management and management of water resources. Due to the need for knowledge about the loss of water from vegetated surfaces, researchers have developed a variety of methods for estimating ETo, some of which are well accepted, while others are criticized, such as the Penman-Monteith-FAO (PM-FAO) meteorological data, which is not always available by limiting its use. The PM-FAO method has been used for decades to be considered internationally and most appropriate for ETo estimates. This method represents the physical phenomenon of evapotranspiration that involves almost all meteorological elements analyzed in automatic and conventional meteorological stations. On the other hand, when this method is impossible to apply due to the lack of some input data, alternative methods are justified (Hargreaves-Samani, Blaney-Criddle, Priestley-Taylor, Jensen-Haise, Camargo, Makkink, Kharrufa , Linacre, Class A tank, Thornthwaite and solar radiation) according to soil and climatic conditions.